Disturbance of traffic noise : evaluation on the effects and management on road corridors - Nur Hazliyana Abdul Mutalib, 1992-, author; Eeydzah Aminudin, 1987-, supervisor; Nordiana Mashros, supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2018